Francisco Antonio Lacaz Netto (1911-1991): um estudo biográfico - Calabria, Angelica Raiz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Francisco Antonio Lacaz Netto was born on 06th February, 1911, in Guaratinguetá, São Paulo state. He graduated in Pharmacy, Geographic Engineering and Mathematics. As professor, he worked only in Mathematics area. He worked at several schools and institutions, one of them the Instituto Tecnológico de Aeronáutica (ITA), located in São José dos Campos, São Paulo, where he was hired as associate university lecturer since its inception in 1950. Besides being university lecturer, Lacaz has invited professionals to make part of the first staff of the Mathematics Department of ITA, they later became important Brazilian researchers. He was head of the Mathematics Department and then dean at ITA. A close friend among the students, he was honoured several times, such as the accolade Lacaz Netto. Professor Lacaz has a considerable bibliography consisting in some mathematical papers and several textbooks. He retired in the ITA in 1981 as professor. Thereby, this research aims to add information to the History of Mathematics in Brazil and It presents a biographical study about Francisco Antonio Lacaz Netto, describing his professional training, university lecturer career, major works and honours, highlighting his career at ITA and also his dedication as professor which present him as Math Educator

Francisco Antonio Lacaz Netto nasceu no dia 06 de fevereiro de 1911 em Guaratinguetá, interior de São Paulo. Graduou-se em Farmácia, Engenharia Geográfica e Matemática. Atuou apenas na área de Matemática como professor. Lecionou em vários colégios e instituições, dentre os quais destacamos o Instituto Tecnológico de Aeronáutica (ITA), localizado na cidade de São José dos Campos, São Paulo, onde foi contratado como professor associado desde sua criação em 1950. Além de professor, auxiliou na primeira composição do quadro docente do Departamento de Matemática do ITA, convidando profissionais que, posteriormente, se tornariam importantes pesquisadores para a Matemática brasileira. Ainda nesse instituto, foi chefe do Departamento de Matemática e, depois, reitor. Era muito amigo dos alunos e recebeu várias homenagens, como a Láurea Lacaz Netto. Professor Lacaz possui uma considerável bibliografia constituída por alguns trabalhos matemáticos e vários livros didáticos. Aposentou-se no ITA como professor titular em 1981. Nesse sentido, o presente trabalho tem como objetivo acrescentar informações à História da Matemática no Brasil e apresentar um estudo biográfico sobre o professor Francisco Antônio Lacaz Netto, descrevendo sua formação, sua carreira docente, suas principais obras e homenagens, privilegiando a sua trajetória no ITA e a sua dedicação como professor, a qual o torna, segundo nossas perspectivas, um educador matemático
Keywords: Instituto Tecnologico de Aeronautica (Brasil); Lacaz Netto, Francisco Antonio 1911-1991; Mathematics - History; Matemática - História; Matematicos; Biografia